1999
DOI: 10.1063/1.479386
|View full text |Cite
|
Sign up to set email alerts
|

The site-specific reactivity of isopropanol in aqueous silicon etching: Controlling morphology with surface chemistry

Abstract: The site-specific rates of isopropanol reaction on Si(111) were studied by kinetic competition with an etchant of known anisotropy and quantified using concentration-dependent changes in the etched surface morphology using a combination of STM measurements and kinetic Monte Carlo simulations. The isopropoxide ion was identified as the active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…Finally, the electrodes were thoroughly rinsed with ultrapure water and dried under nitrogen atmosphere. This chemical etching protocol produces ideal monohydride termination of atomically flat Si(1 1 1) surfaces [35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the electrodes were thoroughly rinsed with ultrapure water and dried under nitrogen atmosphere. This chemical etching protocol produces ideal monohydride termination of atomically flat Si(1 1 1) surfaces [35][36][37].…”
Section: Methodsmentioning
confidence: 99%
“…This defect selectivity makes direct observation of the silicon isopropoxy species very challenging. Nevertheless, motivated by the prediction of Newton et al (1999), Baker et al (2001) have recently observed the presence of the silicon isopropoxy species on highly miscut NH 4 F/d 6 -IPA-etched silicon surfaces using Surface morphology to probe chemical etching 669 infrared absorption spectroscopy. This observation con®rms the proposed reaction sequence.…”
Section: The Mechanism Of Isopropano Lmentioning
confidence: 99%
“…Nucleophilic displacement of hydrogen by alkoxide ions is well known in organosilicon chemistry (Corriu and Guerin 1982). Since this reaction proceeds through the same bimolecular, front-side attack mechanism as the OH ¡ -mediated reaction, Newton et al (1999) proposed that IPA reacts through the analogou s sequential reactions…”
Section: The Mechanism Of Isopropano Lmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the use of alcohols as solvents has been shown to compete with the preferred reaction pathway. 55 Additionally, alcohols are often added to various etching solutions in order to break the surface tension and allow for desired structures (of certain porosity) to be made; 4,16,56,57 in these situations, the surface interaction with the alcohol is significant. 58 Methanol can thus act as a suitable model to understand fundamental surface chemistry for a number of relevant applications.…”
Section: Introductionmentioning
confidence: 99%